Visual short‐term memory for overtly attended objects during infancy. (31st March 2020) - Beckner, Aaron G.; Cantrell, Lisa M.; DeBolt, Michaela C.; Martinez, Marisa; Luck, Steven J.; Oakes, Lisa M.
Abstract: We investigated limitations in young infants' visual short‐term memory (VSTM). We used a one‐shot change detection task to ask whether 4‐ and 8.5‐month‐old infants ( N = 59) automatically encode fixated items in VSTM. Our task included trials that consisted of the following sequence: first a brief (500 ms) presentation with a sample array of two items, next a brief (300 ms) delay period with a blank screen, and finally a test array (2, 000 ms) identical to the sample array except that the color of one of the two items is changed. In Experiment 1, we induced infants to fixate one item by rotating it during the sample (the other item remained stationary). In Experiment 2, none of the items rotated. In both experiments, 4‐month‐old infants looked equally at the fixated item when it did and did not change color, providing no evidence that they encoded in VSTM the fixated item. In contrast, 8.5‐month‐old infants in Experiment 1 preferred the fixated item when it changed color from sample to test. Thus, 4‐month‐old infants do not appear to automatically encode fixated items in VSTM.